Findings of the Association for Computational Linguistics: EMNLP 2020 2020
DOI: 10.18653/v1/2020.findings-emnlp.6
|View full text |Cite
|
Sign up to set email alerts
|

GRACE: Gradient Harmonized and Cascaded Labeling for Aspect-based Sentiment Analysis

Abstract: In this paper, we focus on the imbalance issue, which is rarely studied in aspect term extraction and aspect sentiment classification when regarding them as sequence labeling tasks. Besides, previous works usually ignore the interaction between aspect terms when labeling polarities. We propose a GRadient hArmonized and CascadEd labeling model (GRACE) to solve these problems. Specifically, a cascaded labeling module is developed to enhance the interchange between aspect terms and improve the attention of sentim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Aspect-Opinion Pair Extraction (AOPE) SpanMlt [13], SDRN [11], GTS [75], QDSL [76], SynFue [77] End-to-End ABSA (E2E-ABSA) NN-CRF [78], MNN [79], E2E-TBSA [80], DOER [81], IMN [82], SPAN [83], RACL [84], GRACE [85], IMKTN [86], RF-MRC [87] Aspect Category Sentiment Analysis (ACSA) AddOneDim [88], Hier-GCN [89], BART-generation [90] Triplet Extraction…”
Section: Pair Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aspect-Opinion Pair Extraction (AOPE) SpanMlt [13], SDRN [11], GTS [75], QDSL [76], SynFue [77] End-to-End ABSA (E2E-ABSA) NN-CRF [78], MNN [79], E2E-TBSA [80], DOER [81], IMN [82], SPAN [83], RACL [84], GRACE [85], IMKTN [86], RF-MRC [87] Aspect Category Sentiment Analysis (ACSA) AddOneDim [88], Hier-GCN [89], BART-generation [90] Triplet Extraction…”
Section: Pair Extractionmentioning
confidence: 99%
“…These end-to-end methods can be generally divided into two types [10,78], as shown in Table 3. The first "joint" method exploits the relation between two subtasks via training them jointly within a multi-task learning framework [81,82,84,85,86]. Two label sets including the aspect boundary label (the first row) and the sentiment label (the second row) are adopted to predict the two types of sentiment elements.…”
Section: End-to-end Absa (E2e-absa)mentioning
confidence: 99%
“…Trusca et al extend [36] with deep contextual word embeddings and add an extra attention layer to its high-level representations [34]. To address the imbalance issue and utilize the interaction between aspect terms, Luo et al [24] propose a gradient harmonized and cascaded labelling model based on BERT. Chen et al [7] utilize directional graph convolutional networks to perform end-to-end ABSA task.…”
Section: Aspect-based Sentiment Analysismentioning
confidence: 99%
“…Post-training refers to the process of performing additional unsupervised training to a PLM such as BERT using unlabeled domain-specific data, prior to fine-tuning. It has been shown that this leads to improved performance by helping the PLM to adapt to the target domain [46][47][48][49]. We start with a monolingual PLM in L S and completely adapt it to L T .…”
Section: Transfer Learning As Post-trainingmentioning
confidence: 99%